Improvement in children’s fine motor skills following a computerized typing intervention - McGlashan, Hannah L.; Blanchard, Caroline C.V.; Sycamore, Nicole J.; Lee, Rachel; French, Blandine; Holmes, Nicholas P. (Elsevier, 2017)
Children spend a large proportion of their school day engaged in tasks that require manual dexterity. If children experience difficulties with their manual dexterity skills it can have a consequential effect on their academic achievement. The first aim of this paper was to explore whether an online interactive typing intervention could improve children’s scores on a standardised measure of manual dexterity. The second aim was to implement a serial reaction time tapping task as an index of children's finger movement learning, and to see whether performance on this task would improve after the intervention. Seventy-eight typically developing children aged between 8 and 10 were tested at their school on the pre-intervention Movement Assessment Battery for Children (2 nd edition; MABC-2) and tapping tasks. Twenty-eight of these children volunteered to be randomly allocated to the intervention or control group. Children in the intervention group had a choice of two online games to play at home over a period of four weeks, while the children in the control group were not given these games to play. The intervention and control groups were then re-tested on the MABC-2 manual dexterity and the tapping task. Children in the intervention group significantly improved their manual dexterity scores in the MABC-2 compared to the control group. On average, all children learnt the tapping sequence, however, there were no group differences and no effect of the intervention on the tapping task. These results have important implications for implementing a freely available, easy to administer, fun and interactive intervention to help children improve their manual dexterity skills.